The Great American Road Trip : Roam the Roads From Coast to Coast. - Smith, Jonah, ....-; Aether; West, Palmer, ....-; Austin, Laura, 1987- (Berlin : gestalten, 2022)
When it comes to the great outdoors, the USA has it all: wild mountains, vast prairies, barren deserts, tropical forests and other worldly canyons. And there is no better way to explore them than that all-American activity: the road trip. The Great American Road Trip provides a new appreciation of this grand tradition. Leading beyond magnificent landscapes and seeking out history, culture, food, and people; Retrace the Underground Railroad, follow the Blues Highway, go on a pilgrimage to the best lobster shacks. The Great American Road Trip encourages readers to start an adventure of their own. So what are you waiting for? The road awaits...
Keywords: Reizen